Religion and Public Policy: Digital-Based Islamic Political Economy and Human Security on Covid-19 Handling - Sri Haryaningsih; Elyta Elyta (Graduate Program of Pontianak Institute of Islamic Studies, 2022)
Covid-19 has become a pandemic causing the condition of business income from business actors to decrease drastically. This phenomenon is in contrast to the conditions in Indonesia during the 1998 crisis, where business actors became the most substantial sector to adapt to the monetary turmoil at that time. This article discusses the Covid-19 handling through digital-based Islamic political economy and human security on business people in Pontianak City. The work is based on a quantitative research project conducted in Pontianak, employing a set of questionnaires to collect the data. The findings of this study indicate that in dealing with Covid-19, the Indonesian government has produced important policies to ensure the availability of economic opportunities for the population so that people can adapt rationally sound state policies. The handling of Covid-19 through a digital-based Islamic political economy is carried out by providing digital technology training and mentoring digital business incubators to Small and Medium Enterprises to improve human security. Islamic teachings have been important to the policy making as Indonesia is a home of predominantly Muslims.